Dynamic analysis of the flexible protection system for electricity transmission engineering - Y. Gu; Z. Gu; Z. Yu; P. Lan; N. Lu (Mechanical Sciences, 2025)
Due to the low cost and short erection period, the flexible protection system is gradually replacing the traditional cross-frame design based on a large steel structure and becoming the main means of protection in power construction. The accurate dynamic analysis of the process of wire falling into a nylon rope net after tension failure is the key to the design and optimization of the flexible protection system. Efficient modeling and analysis of rope network are the core problems. In this investigation, the absolute nodal coordinate formulation cable element is used to model the transmission wire and the nylon rope net. The form finding of the net is performed based on the iterative force density method. The static condensation method is introduced to perform the dynamic analysis of the net to ensure the simulation efficiency. An experiment is carried out to verify the proposed modeling and analysis method. Configurations are compared between the simulation and experimental results so that the feasibility of the proposed method can be demonstrated.